ROS-induced near-homozygous genomes in thyroid cancer. Issue 1 (January 2018) - Corver, Willem E; Demmers, Joris; Oosting, Jan; Sahraeian, Shima; Boot, Arnoud; Ruano, Dina; Wezel, Tom van; Morreau, Hans
Abstract : A near-homozygous genome (NHG) is especially seen in a subset of follicular thyroid cancer of the oncocytic type (FTC-OV). An NHG was also observed in the metabolically relatively quiescent cell lines XTC.UC1, a model for FTC-OV, and in FTC-133, -236 and -238, the latter three derived from one single patient with follicular thyroid cancer. FTC-236 subclones showed subtle whole-chromosome differences indicative of sustained reciprocal mitotic missegregations. Reactive oxygen species (ROS) scavenger experiments reduced the number of chromosomal missegregations in XTC.UC1 and FTC-236, while pCHK2 was downregulated in these cells. Treatment with antimycin A increased ROS indicated by enhanced MitoSOX Red and pCHK2 fluorescence in metaphase cells. In a selected set of oncocytic follicular thyroid tumors, increasing numbers of whole-chromosome losses were observed toward an aggressive phenotype, but with retention of chromosome 7. Together, ROS activates CHK2 and links to the stepwise loss of whole chromosomes during tumor progression in these lesions. We postulate that sequential loss of whole chromosomes is a dominant driver of the oncogenesis of a subset of follicular thyroid tumors.